PENGALAMAN PENGASUH DALAM MERAWAT LANSIA DENGAN PENYAKIT KRONIS REMATIK DI WILAYAH JANGKAUAN LKS LU MANDAR INDONESIA DESA BUKU - Hardikai Ikahardika; Fredy Akbar K; Hamdan Nur Hamdan (Bina Generasi : Jurnal Kesehatan, 2022)
The aging process is a life cycle characterized by the decline in various organ functions in the body which is marked by the susceptibility of the body to various disease attacks. As for the changes, it affects the deterioration of physical health which in turn will affect the susceptibility to disease. Rheumatic disease and joint inflammation are diseases that are often found in the community, especially in people aged 40 years and over. More than 40 percent of these age groups suffer from complaints of joint and muscle pain. This study aims to determine the experience of caregivers in caring for the elderly with chronic rheumatic disease in Buku Village, Mapilli District, Polewali Mandar Regency, West Sulawesi Province. . The method used in this research is to use qualitative research where this research is a method to find answers to elderly cargiver. The sample was 5 elderly respondents who were made as respondents. Results of the study] The experience of caregivers in caring for the elderly with chronic rheumatic disease, there were 5 respondents who were carried out by the research. From the results of the conversation above, it can be concluded that the Caregiver plays an important role in treating the Elderly with Chronic Rheumatic Disease.